The Morphometric Analysis of Kidney Development in Human Fetuses - Çiçekcibaşı, Aynur Emine; Ziylan, Taner; Büyükmumcu, Mustafa; Tuncer, İşık; Murshid, Khalil Awadh (Fırat University, 2002)
Aim: In this study, localization of kidneys and their morphometric development were evaluated in human fetuses, and obtained data were analyzed statistically. Material and Methods: The study was carried out on 61 second trimester and 29 third trimester spontaneously aborted human fetuses, totally 90, of whom 45 were male and 45 female. 180 kidneys were inspected through bilateral dissections under the vision of operating microscope. The localizations of the kidneys according to the columna vertebralis were found out. Furthermore, the length, width and thickness of the kidneys were measured with electronic calipers, and they were photographed. Data were analyzed through a computer software (SPSS for Windows 10.0) with Mann-Whitney U test and Pearson correlation test. Results: Although there was no significant difference between the average length, width and thickness of both kidneys in terms of gender and lateralization, there was significant difference between the trimesters (p

Amaç: Çalışmada, insan fötuslarında böbreklerin lokalizasyonu ve morfometrik gelişimi değerlendirilerek, elde edilen verilerin istatistiksel analizi yapıldı. Gereç ve Yöntem: Çalışma, 61 ikinci trimestr, 29 üçüncü trimestr olmak üzere toplam 90 (45 erkek, 45 dişi) adet spontan abort fötusta gerçekleştirildi. Mikrocerrahi mikroskobu altında, çift taraflı yapılan diseksiyonlar ile 180 adet böbrek incelendi. Böbreklerin columna vertebralis'e göre lokalizasyonları belirlendi. Ayrıca uzunluk, genişlik ve kalınlık ölçümleri elektronik kumpas yardımı ile yapıldı ve fotoğrafları çekildi. Veriler SPSS programında (Windows için 10.0) Mann-Whitney U testi ve Pearson korelasyon testi ile istatistiksel olarak değerlendirildi. Bulgular: Her iki böbreğin uzunluk, genişlik ve kalınlık ortalamalarında, cinsiyetler ve lateralizasyon açısından anlamlı farklılık gözlenmemesine karşılık, trimestrlar arasında anlamlı farklılık (P
İNSAN FÖTUSLARINDA BÖBREK GELİŞİMİNİN MORFOMETRİK ANALİZİ